Budidaya Bekicot Desa Sukolilan Kabupaten Kendal sebagai Prospek Usaha Masyarakat Desa - Deo Renaldi Saputra; Warist Al Wasi; Nurul Latifah; Aura Putri Salsabilla; M. Aslam Ramadhan; Muhammad Syarif Hidayat (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
The Sukolilan Village community's efforts to strengthen the rural economy through animal husbandry is one example of community activities that can boost the rural economy. Snail farming is a business prospect for the village community because it is very easy to cultivate. This research uses a descriptive qualitative method with data obtained through direct surveys to snail cultivators. The results of this study can provide an understanding that snail cultivation has a great opportunity to be practiced and expanded to improve the village economy.